Polymorphisms in the dopamine D2 receptor gene and their relationships to striatal dopamine receptor density of healthy volunteers - Jönsson, E G; Nöthen, M M; Grünhage, F; Farde, L; Nakashima, Y; Propping, P; Sedvall, G C (Molecular psychiatry, 1999)
The density of striatal dopamine D2 receptors has been shown to vary considerably among healthy subjects. 1 This variability might be due to genetic or environmental factors. In the present analysis we searched for relationships between dopamine D2 receptor gene (DRD2) polymorphisms and striatal dopamine D2 receptor density in vivo , as measured by positron emission tomography and [ 11 C]raclopride in 56 healthy subjects. There was a significant association between presence of a putative functional DRD2 promoter allele (−141C Del) and high striatal dopamine receptor density ( t = 2.32, P = 0.02). In agreement with some previous studies 2–4 the presence of the DRD2 TaqIA1 allele was associated with measures of low dopamine receptor density ( t = 2.58, P = 0.01). Also the DRD2 TaqIB1 allele was associated with low dopamine receptor density ( t = 2.58, P = 0.01) wheras there was no significant relationship between another common silent intronic DRD2 short tandem repeat polymorphism (STRP) and striatal dopamine D2 receptor density. The results suggest that DRD2 genotypes may participate differentially in the regulation of striatal dopamine D2 receptor density in healthy human subjects. The results should be interpreted with caution because of the limited sample size.